2020
DOI: 10.1128/jcm.00958-20
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Inactivation Methods on Severe Acute Respiratory Syndrome Coronavirus 2 RNA Copy Number

Abstract: The outbreak of COVID-19 has spread across the world and was characterized as a pandemic. To protect medical laboratory personnel from infection, most laboratories inactivate the clinical samples before testing. However, the effect of inactivation on the detection results remains unknown. Here, we used a digital PCR assay to determine the absolute SARS-CoV-2 RNA copy number in 63 nasopharyngeal samples and assess the effect of inactivation methods on viral RNA copy number. Viral inactivation was performed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 18 publications
3
58
0
Order By: Relevance
“… 48 Incubating samples at 56 °C for 10 min, has been shown to completely denature the nucleocapsid protein of SARS-CoV 48 and similarly heating plasma at 56 °C for 25 min reduced >4 log 10 TCID 50 /mL of MERS virus, 49 where TCID 50 represents the median tissue culture infectious dose. Since heat treatment has been recommended for viral inactivation, and there is a reported study 50 which demonstrated the generation of false negative results, we therefore compared the effect of heating on the 1 H NMR-derived lipoprotein profile, CPMG and 1D spectral data sets. Heating samples at 56 °C for 30 min caused major changes across all three spectral data sets.…”
Section: Resultsmentioning
confidence: 99%
“… 48 Incubating samples at 56 °C for 10 min, has been shown to completely denature the nucleocapsid protein of SARS-CoV 48 and similarly heating plasma at 56 °C for 25 min reduced >4 log 10 TCID 50 /mL of MERS virus, 49 where TCID 50 represents the median tissue culture infectious dose. Since heat treatment has been recommended for viral inactivation, and there is a reported study 50 which demonstrated the generation of false negative results, we therefore compared the effect of heating on the 1 H NMR-derived lipoprotein profile, CPMG and 1D spectral data sets. Heating samples at 56 °C for 30 min caused major changes across all three spectral data sets.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to qualitative diagnosis, quantitative detection also plays a significant role in COVID-19 diagnosis, surveillance, prevention, and control. As a technology for the absolute quantification of nucleic acids, digital polymerase chain reaction (dPCR) has also been applied to SARS-CoV-2 nucleic acid detection [4] , [5] , [6] . In a dPCR assay, the sample is first diluted and evenly partitioned into many independent reaction chambers.…”
Section: Introductionmentioning
confidence: 99%
“…Higher C t values for thermally treated samples may suggest a reduction in detectable virus RNA. A recent study using a commercial qualitative method (BioGerm Medical Biotechnology, Shanghai, China) and quantitative digital PCR (TargetingOne, Beijing, China) demonstrated a drop in SARS-CoV-2 copy number by 50% to 66% after heating at 80°C for 20 minutes [ 8 ]. However, internal control test performance was not evaluated (or not included as part of the assay), and correlation with other commercial in vitro diagnostic assays or cobas is not known.…”
mentioning
confidence: 99%